Open-access satellite data for peatland condition and restoration monitoring in the UK: a review - Reynolds, Nicole; Mota, Bernardo; Nightingale, Joanne M. (Frontiers in Environmental Science, 2025)
This paper presents a literature review of satellite remote sensing approaches for monitoring northern peatland condition indicators. First, a set of key climate regulation indicators related to hydrology, vegetation, and terrain changes is identified and evidenced. Second, satellite remote sensing methods to measure and monitor each indicator are summarized and assessed. Finally, recommendations on the utility of open-access satellite data to monitor peatland condition indicators of northern peatlands in an operational context are provided. Results of this study demonstrate that a combination of data from both radar and optical satellites, reinforced by robust ground and aerial measurements for calibration and validation, is able to track temporal and spatial changes of the key indicators. Operational monitoring of peatland condition and change resulting from restoration activities can underpin carbon crediting mechanisms. Satellite data enables systematic, national-scale monitoring of peatland restoration over extended timeframes. However, challenges such as obtaining cloud-free optical imagery remain. Future satellite missions will allow for further development of remote sensing methods to improve peatland condition monitoring.